Uji performance turbin Savonius dengan penambahan konsentrator pada aliran air - Alit, I.B.; Mara, I.M.; Susana, I.G.B.; Sapri, S. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2019)
Utilization of water energy is essentially using potential energy and kinetic energy, kinetic energy flow of water which is a transformation of gravitational potential energy is used to drive turbines or waterwheels, Savonius turbine has a good Self Starting so it can rotate the rotor even though the fluid speed is low, the same thing the speed of the water flow has a low speed. The purpose of this research is to know the influence of the number of blades on rotation of rotor (n), Torque (T), Rotor power (P), Coefficient of performance (CP), Efficiency system (ɳs), in this study the number of blades used are 2 blades, 3 blades and blades, the blades are then tested without the use of concentrator and by the addition of concentrator. The results of this study indicate that the turbine without concentrator or by using the addition of concentrator obtained the best performance on the number of blade 3 with average CP of 0.12 and 0.13 efficiency system of 9.83% and 11.75% then with the number of blades 2 with CP averaging of 0.10 and 0.11 of efficiency system of 8.73% and 11.00% and the number of 4 blades with CP averaged 0.06 and 0.07 and efficiency system of 3.91% and 4.76%. Using the addition of concentrator may increase the performance of the turbine in water flow savonius seen from the increasing value of CP and system efficiency at each number of blades tested.